Parents' Investment in English for Young Learners: The Case of Elementary School Students Attending Non-Formal English Education - Farahdina, Nuria; Petrus, Ismail; Silvhiany, Sary (Universitas Jambi, Indonesia, 2023)
This research seeks to explore parents' investment in English for young learners. Nowadays, English is not a compulsory lesson in state elementary schools in Indonesia. However, parents invested their children in non-formal English education. This research offers the point of view of state elementary school students' parents regarding English education at an early age. This research implemented a qualitative with a case study approach. It involved six parents of state elementary school students. The data were collected through semi-structured interviews and demographic questionnaires. The interview data were analyzed using thematic analysis. This research finding indicated that all parents had high or positive expectations after their children joined an English course. The main factor indicating this was that English is not a compulsory lesson anymore in Indonesian state elementary schools. Thus, the parents' involvement in supporting their children to learn English made them practice it at home and in additional English courses.